Experimental investigation of variations in morphology, composition and mixing-state of boundary layer aerosol: A balloon based study over urban environment (New Delhi). (July 2018) - Mishra, S.K.; Ahlawat, A.; Khosla, D.; Sharma, C.; Prasad, M.V.S.N.; Singh, Sukhvir; Gupta, B.; Tulsi,; Sethi, D.; Sinha, P.R.; Ojha, D.K.; Wiedensohler, A.; et al.
Abstract: The morphology, composition, and complex mixing states of aerosol are extremely important physico-chemical properties which are the major inputs to the optical/radiative models. Though, ground based observations of the said properties are abundant but the vertical profiles of the same are very much limited throughout the globe. The information on the vertical heterogeneity of the aforementioned properties over a polluted environment like Delhi will be very helpful to develop a better understanding of the thermodynamics of the lower atmosphere. In present study, we carried out a tethered balloon based field campaign in National Physical Laboratory (28° 38′ 10″ N, 77° 10′ 17″ E) from 21 to 27 February 2014 to explore the vertical distribution of the said properties. Based on the microscopic observations, the bubbly shaped sulfate particles number percentage is less (5%) on the ground, abundant (49%) on altitude <350 m and nearly absent on altitude >350 m. At 500 m altitude, particles were majorly of spiked shape with elongated dimension ∼ 3–4 μm. The number percentage of the aged fractals has been found to increase by 4% in the 100–350 m range against the ground observations. Based on the bulk composition of non-carbonaceous species, at 200 m altitude, we observed significant amount (74%) of the oxides of sulfur compared to that of ground observations (30%) that could be due to temperature inversion and air parcel movement from IGP (Indo Gangetic Plain). Various core-shell type particle configurations have been observed at different altitudes. At 200 m altitude, particles were majorly aged with anionic species (like S, Cl and HSO4) and cationic species (like C2H5). The bulk and individual particle level data generated over Delhi environment in this experiment may improve our understanding of boundary layer aerosol and could provide the scientific insights of their probable effects on low level cloud formation. Graphical abstract: Image 1 Highlights: Observation of morphology, composition, and complex mixing states of boundary layer aerosol collected at varying altitude (ground to 700 m) using tethered balloon in National Physical Laboratory (28° 38′ 10″ N, 77° 10′ 17″ E) from 21 to 27 February 2014. The generated data will lead to better understanding of the thermodynamics of the lower atmosphere. Based on the bulk composition of non-carbonaceous species, at 200m altitude, we observed significant amount (74%) of the oxides of sulfur compared to that of ground observations (30%) that could be due to temperature inversion and air parcel movement from IGP (Indo Gangetic Plain). In general, based on TOF-SIMS analysis, particles at various altitudes were found to be aged with C2H5+, Na+, K+, Cl-, HSO4¬-. The vertical distribution of Black Carbon (BC) morphologies show that fresh, semi-aged and aged fractals have been observed to be dominant at altitudes < 350 m compared to that of >350 m. Noteworthy to mention that for a given size, the optical properties of BC particles are very sensitive to their morphologies. Vertical profile of hematite weight percentage in the dust has been reported. Noteworthy to mention that hematite is the major component in the dust which gives rise to absorption of shortwave radiation.